1843. Prescribers' Characteristics and Unnecessary/Inappropriate Antimicrobial Prescription in the Emergency Department: An Observational Study at a Tertiary Care Center. (26th November 2018) - Tagashira, Yasuaki; Yamane, Naofumi; Miyahara, Satoshi; Orihara, Azusa; Uehara, Yuki; Hiramatsu, Keiichi; Honda, Hitoshi
Abstract: Background: Antimicrobials are commonly prescribed in the emergency department despite the fact that a large proportion of these drugs are misused. However, comprehensive studies of factors leading to the misuse of antimicrobials in the emergency department (ED) are few. Understanding current practice of antimicrobial use in the ED is important for developing an effective antimicrobial stewardship program for this setting. Methods: We performed a 1-year cohort study of patients discharged from the ED in a tertiary care center with a prescription for oral antimicrobial agents. A retrospective audit of the appropriateness of antimicrobial prescription using prespecified criteria was performed by two infectious disease physicians. Patterns in antimicrobial prescription and the physician-, patient-, and environment-related factors predicting unnecessary/inappropriate antimicrobial prescription were evaluated. Results: Of the 36, 308 annual visits to the ED, 1, 555 patients (4.3% of visit) received oral antimicrobial prescriptions upon discharge. Pneumonia (18.2% [283/1, 555]) was the most common indication for antimicrobial prescription. Of the 1, 555 antimicrobial prescriptions issued, 852 (52.9%) were considered inappropriate. Factors significantly associated with unnecessary/inappropriate antimicrobial prescription included the lack of comorbidities (adjusted odds ratio [aOR]: 1.39; 95% confidence interval [CI]: 1.03–1.87), late-night visit (aOR: 1.48 95%; CI: 1.05–2.09), the spring-summer season (aOR: 1.13 95%; CI: 1.03–1.25), higher postgraduate year (>10 years) (aOR: 1.77 95%; CI: 1.24–2.52), and physicians in surgical subspecialties (aOR: 4.51 95%; CI: 3.34–6.09). Conclusion: More than half of oral antimicrobial prescriptions in the ED were inappropriate. Unnecessary or inappropriate antimicrobial prescriptions were frequently issued during the late-night shift, and by older physicians and physicians in surgical subspecialties. Disclosures: All authors: No reported disclosures.